Brat Albert i jego czasy w naszych czasach. Marek Sołtysik „Znak miłości. Opowieść o Adamie Chmielowskim – Świętym Bracie Albercie” - Głąb, Grzegorz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Sołtysik’s story is devoted to the life and activity of Brother Albert Chmielowski. It is also a work about the phenomenon of holiness, which the author tries to diagnose and describe its distinctive features. Reading The Sign of Love allows us to say that the author of the work depended on the objective and material presentation of the figure of the Father of the Poor, so most of the descriptions and dialogues constructed by him were based on archival materials - documents, letters and opinions of Brother Gray or people directly knowing him. The storyline of this biographical setting is governed by the chronology of events, but the author first explores the themes of the Holy Life, which allow for a spiritual portrait of the hero, as well as answering questions about the source of his conversion, spiritual calling and holiness. Marek Sołtysik, developing the thesis that saints express their times and at the same time overtakes them, tries to convince readers that Brother Albert is also a man of our age, because his spiritual profile and apostolate indicate timeless and cross-generational values – faith, loveand human dignity.